Coaching psychology : catalyzing excellence in organizational leadership - Vandaveer, Vicki V.; Frisch, Michael H. (Fundamentals of consulting psychology book series., 2022)
"Coaching psychology offers a science-based approach for nurturing personal and professional growth. This concise guide helps prepare psychologists to work with individuals in an organizational setting to develop their leadership skills. It offers a complete overview of coaching psychology, from initial contact to termination of the engagement. The coaching psychologist draws upon myriad tools including assessment inventories and video recordings of the client, to help evaluate current performance and areas for improvement. Research demonstrating the effectiveness of various coaching methods is provided, along with practical discussions of how psychologists can acquire the often subtle skills required to become effective coaches. Common ethical dilemmas such as how to handle multiple relationships are also examined, along with evidence-based strategies for addressing professional issues such as maintaining emotional resilience"--